Studentsâ Perspective on the Domains of Teaching Quality - Suarman, Suarman (EDUCARE, 2015)
ABSTRACT: This study is aimed to evaluate the teaching and learning quality at the UNRI (University of Riau), which currently ranked at the top 21 best Indonesian universities and ranked at the 2,185 of the world universities ranking. The UNRI was chosen because it is the top university at the Riau Province and it offers various fields of study. The research population is all registered students for the year 2010 academic session. The instrument to test the teaching quality is adapted from a study conducted by M.D. Toland & R.J. de Ayala (2005). In overall, it was found that the lecturersâ teaching and learning quality is at the low level for the domain of course subject. Students reported that the teaching and learning dynamic is also very low, particularly due to the lecturersâ failures in integrating various methods. In addition, the absence of active interaction process is because it is very exam oriented and the lessons are normally conducted one way with only a little option for question and answer session. This result shows that students prefer to find other sources of information regarding the content of the course, instead of meeting and consulting the lecturers. In overall, the lecturersâ quality is only average which needs improvement in the aspects of teaching motivation, teaching approaches, maintaining relationship with students, efficiency, assessment, and assignments. Other than that, the result also shows the quality is at the low level for the list of courses and students relationship in the context of academic development. Obviously, the teaching and learning quality of lecturers in the UNRI needs to be upgraded in order to improve the image of the university and to attract more new students domestically, regionally, and internationally.KEY WORDS: Educational service quality, student satisfaction, quality teaching, motivation, teaching approach, academic development, and image of the university.About the Author: Dr. Suarman is a Senior Lecturer at the Faculty of Education UNRI (University of Riau), Kampus Bina Widya Km. 12,5 Simpang Baru, Pekanbaru 28293, Riau, Indonesia. For academic purposes, the author can be contacted via e-mail at: suarman6688@gmail.comHow to cite this article? Suarman. (2015). âStudentsâ Perspective on the Domains of Teaching Qualityâ in EDUCARE: International Journal for Educational Studies, Vol.7(2) February, pp.171-180. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (January 22, 2015); Revised (February 2, 2015); and Published (February 28, 2015).